Legal sex, self-classification and gender self-determination. Issue 1 (2nd January 2017) - Hutton, Christopher
ABSTRACT: This paper discusses legal sex in the context of transgender jurisprudence, reviewing arguments for individual agency, elective categories and ideas concerning or 'self-sovereignty'. It is argued that legal sex has no explicit foundation in case law or statute, and that it was effectively brought into being by the decision in Corbett v Corbett (otherwise Ashley) [1971] P 83. In Corbett the judge could simply have ruled that the birth certificate was determinative unless refuted by medical testimony (ie a clear mistake on its face) – instead he embarked on ontological investigation of sexual identity. That decision, paradoxically, denied that there was a category of legal sex 'at large', and argued that it was primarily the law of marriage that reflected sex. In other legal domains, gender identity or psychological sex could be recognized. However Corbett was treated as setting out criteria for legal sex, this understood as grounded in bodily ontology or 'sexed being'. Reviewing arguments for self-determination, self-classification or self-ownership in relation to sexual identity, the paper concludes that there is no way for law to capture the lived ontology of sexual identity or gender. It was Corbett that gave the impetus for this approach, and even now that Corbett has been rejected, various attempts were being made to create a fit between the ontological or experiential category and legal sex. This is in principle impossible, given the diversity of identity narratives that exists in society. Legal sex, if it is required at all, needs to be understood in non-essentialist terms.